Antimicrobial efficacy of an apical negative pressure root canal irrigation system against intracanal microorganisms. (May 2018) - Zeng, Chang; Meghil, Mohamed M.; Miller, Marcus; Gou, Yaping; Cutler, Christopher W.; Bergeron, Brian E.; Niu, Lina; Ma, Jingzhi; Tay, Franklin R.
Abstract: Objectives: The effect of irrigation time on the antimicrobial efficacy of an apical negative pressure irrigation system was examined in vitro, followed by validation of the antimicrobial effect in vivo using the identified optimal irrigation time. Methods: For the in vitro experiment, 44 extracted premolars were decoronated, instrumented, autoclaved and inoculated with Enterococcus faecalis (ATCC 29212) for 21 days. Four teeth were used as positive control, without irrigation. Each of the remaining 40 teeth was irrigated with 2.5% NaOCl, delivered via the EndoVac MacroCannula for 10 s, and subsequently via the EndoVac MicroCannula for 15, 30, 45, 60 or 90 s per canal, respectively (N = 8). After irrigation, microbial samples were collected, transferred to BHI broth and incubated for counting of bacterial colony forming units (CFUs). Based on the in vitro results, 8.25% NaOCl was delivered via the EndoVac MicroCannula for 60 s, during root canal treatment of 20 human subjects presented with apical periodontitis. Microbial samples retrieved in vivo prior to canal instrumentation (S0), after chemomechanical debridement (S1) and after irrigation with EndoVac (S2) were cultured in an anaerobic chamber for 7 days for CFU evaluation. Results: Compared with the control, irrigation significantly reduced bacterial populations (p < .05). Irrigation delivery via the EndoVac demonstrated improved antibacterial efficacy with increased irrigation time (p < .05). Samples retrieved from canals after NaOCl delivery in vivo with the EndoVac for 60 s were all culture-negative. Conclusions: Microbial elimination may be achieved with 8.25% NaOCl delivered via the EndoVac apical negative pressure irrigation device for 60 s. Clinical significance: With the use of the EndoVac apical negative pressure irrigant delivery system, optimal elimination of the intracanal bacterial load can only be achieved when sodium hypochlorite is delivered via the MicroCannula for at least 60 s per canal.